2017
DOI: 10.1002/pds.4363
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vascular complications associated with interferon‐ribavirin therapy for chronic hepatitis C: A population‐based study

Abstract: Interferon-ribavirin therapy was associated with a 53.3% increased risk of retinal vascular complications compared with not receiving the therapy. Regular ophthalmologic examination is essential for patients receiving interferon-ribavirin, particularly those with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…[6] IFN-α (İnterferon α) etkisi ile retinal vasküler komplikasyon görülme riski %53 olarak bildirilmiştir. [7] IFN-α kullanımına bağlı gelişen retinopatide riski artıran faktörler; diyabet, hipertansiyon, ilacın dozu, hemoglobin değeri ve pegile-IFN kullanımıdır. [6,[8][9][10] Birçok hastada retinal toksisite asemptomatik seyreder, fakat fundustaki değişiklikler tedavinin 12. haftasında görülmeye başlar ve genelde asemptomatiktir.…”
Section: Interferonunclassified
“…[6] IFN-α (İnterferon α) etkisi ile retinal vasküler komplikasyon görülme riski %53 olarak bildirilmiştir. [7] IFN-α kullanımına bağlı gelişen retinopatide riski artıran faktörler; diyabet, hipertansiyon, ilacın dozu, hemoglobin değeri ve pegile-IFN kullanımıdır. [6,[8][9][10] Birçok hastada retinal toksisite asemptomatik seyreder, fakat fundustaki değişiklikler tedavinin 12. haftasında görülmeye başlar ve genelde asemptomatiktir.…”
Section: Interferonunclassified
“…Many studies have reported the detection of HCV and its antigen in the tears and aqueous humor of seropositive patients [ 13 , 14 , 15 , 16 , 17 , 18 ]. In addition, HCV infection has been indicated to be associated with many ocular pathophysiologies such as acute vision loss [ 19 ], retinopathy [ 20 , 21 ], retinal pigment epithelitis [ 22 ], uveitis [ 23 ], cataract [ 24 ], and dry eye disease [ 25 , 26 ]. Recently, dry eye disease [ 25 ] and ischemic retinopathy caused by either HCV-induced vasculitis [ 20 ] or interferon treatment [ 25 , 26 ] have been reported to be strongly associated with the ocular manifestations of HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HCV infection has been indicated to be associated with many ocular pathophysiologies such as acute vision loss [ 19 ], retinopathy [ 20 , 21 ], retinal pigment epithelitis [ 22 ], uveitis [ 23 ], cataract [ 24 ], and dry eye disease [ 25 , 26 ]. Recently, dry eye disease [ 25 ] and ischemic retinopathy caused by either HCV-induced vasculitis [ 20 ] or interferon treatment [ 25 , 26 ] have been reported to be strongly associated with the ocular manifestations of HCV infection. The pathogenesis of ocular changes may be the direct action of viral and immunological reactions to certain viral antigens and even immune complexes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these ocular syndromes were reported in small case series and individual patients. In a retrospective cohort study involving 4736 patients from the Taiwan National Health Insurance (NHI) Research Database, Lai et al (2018) indicated that the risk of retinopathy was 1.53 times higher in patients receiving interferon-ribavirin therapy for HCV infection than in patients with HCV not receiving the therapy (95% confidence interval (CI), 1.14-2.06; p = 0.0048) [16]. Nevertheless, the study did not adjust for all potential confounding factors or evaluate retinopathy subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the study did not adjust for all potential confounding factors or evaluate retinopathy subtypes. Furthermore, studies have suggested that patients with HCV and comorbidities such as diabetes and hypertension have an increased risk of ocular complications, but the results have been inconsistent [16,17].…”
Section: Introductionmentioning
confidence: 99%